A Patient- and Function-Centric Model/Approach for Hypoglycemia Management in Older Adults - Kannayiram Alagiakrishnan; Laurie Mereu; Gulelala Rahim; Mahua Ghosh; Albert Vu (Geriatrics, 2026)
Diabetes-related hypoglycemia contributes substantially to increased morbidity, mortality, health-care utilization, and reduced quality of life. Older adults with diabetes represent a heterogeneous group of patients who need individualized blood glucose targets to avoid hypoglycemia. Since the elderly present with varying degrees of functional and cognitive status and individualized health needs, their management varies among individuals. Complicating this, the hypoglycemia risk in older adults treated with insulin also varies due to aging, renal dysfunction, cognitive impairment, and other comorbidities. The challenge for healthcare providers is in considering all aspects of care in order to avoid hypoglycemia in elderly individuals. In this review, we introduce a Patient and Function Centric Approach to the assessment and management of hypoglycemia in older adults. This holistic framework extends beyond blood glucose values to systematically evaluate the other domains of patients’ health that influence hypoglycemia risk, including biochemical, medication, timing, autonomic, cognitive, mood, renal, pancreatic, hepatic, social, and physical function. The management of hypoglycemia in older adults should also include strategies to address both fear of hypoglycemia and hypoglycemia unawareness. In addition to physical limitations, the psychosocial barriers to self-care in older individuals with hypoglycemia are also of paramount importance. Using tools that measure diabetes burden, diabetes distress, and fear of hypoglycemia provides valuable insights into patient wellbeing. The use of newer anti-hyperglycemic medications, sensor-augmented insulin pump therapy, intranasal glucagon, and continuous glucose monitoring (CGM) has significantly contributed to reduced hypoglycemia incidence in individuals with diabetes. Overall, successful management requires a collaborative approach that empowers patients, respects their individual needs and preferences and helps them face the challenges associated with diabetes management with confidence rather than fear or anxiety. Adopting a patient- and function-centric approach to hypoglycemia management allows clinicians to move beyond a one-size-fits-all model and adopt individualized glycemic targets that improve overall diabetes control and mental well-being.